1999
DOI: 10.1063/1.873536
|View full text |Cite
|
Sign up to set email alerts
|

Mach numbers for gases and plasmas in a convergent-divergent cascaded arc

Abstract: For a plasma, flowing through a cascaded arc channel with a varying cross-section, and flowing from a subsonic to a supersonic state, the sonic condition moves downstream and the plasma Mach number at the smallest cross section is less than one, although in case of a transonic isentropic gas flow the sonic condition is found at the smallest cross section. This shift in sonic condition is due to the lack of isentropic behavior of the plasma flow. Sources causing the anisentropy are viscosity, heat and ionizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 12 publications
5
24
0
Order By: Relevance
“…A second one is the relevance of ionization and collisional process in the real plasma plume, also neglected in the model. Incidentally, collisions would also justify that the sonic point is here placed inside the divergent nozzle and not at a MN throat [39,40]. And finally, discrepancies should not be attributed exclusively to the theory.…”
Section: Resultsmentioning
confidence: 98%
“…A second one is the relevance of ionization and collisional process in the real plasma plume, also neglected in the model. Incidentally, collisions would also justify that the sonic point is here placed inside the divergent nozzle and not at a MN throat [39,40]. And finally, discrepancies should not be attributed exclusively to the theory.…”
Section: Resultsmentioning
confidence: 98%
“…ionization), is lower than the adiabatic value. In particular, as a consequence of the different behaviour of constant pressure and constant volume specific heats, it is found that their ratio is constant also for plasmas [59], provided the degree of ionization lies between 5% and 80%. For an atmospheric plasma, whose temperatures are of the order of the eV, γ=1.16 instead of the γ=1.4 valid for ordinary gases.…”
Section: Sound Velocitymentioning
confidence: 98%
“…In [36] and more recently in Burm et al [59], it is stated that the Mach number of a plasma is always lower than the corresponding value for the gas. This is a consequence of the value of the isentropic exponent in plasma that, due to additional degrees of freedom with respect to the ordinary gas (e.g.…”
Section: Sound Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…The lower isentropic exponent upstream the flat plate has a direct influence on the interaction between the supersonic gas flow and the flat plate and, then, on the shock wave. A modification of the isentropic exponent leads to a change in the velocity of the flow and the Mach number [29,51]. To evaluate this effect we used the Barré de Saint-Venant equation to estimate the flow velocity upstream of the flat plate when the plasma actuator is switched on.…”
Section: Analysis Of Ionization Degree In the Shock Wave Angle Increasementioning
confidence: 99%